Export of particulate organic carbon (POC) in the eddy region of the tropical northwest Pacific - Seo, Junhyeong; Kim, Guebuem; Park, Jae-Hyoung; Seo, Hojong; Na, Taehee; Kang, Sok Kuh; Hwang, Jeomshik (Frontiers in Marine Science, 2022)
We examined particulate organic carbon (POC) export using 238U–234Th disequilibrium in the tropical northwest Pacific Ocean, where numerous eddies are present. We obtained data from an anticyclonic eddy in 2019 and from both anticyclonic and cyclonic eddies in 2020. In 2019, excess 234Th and higher POC concentrations were observed in the upper 100 m layer inside the anticyclonic eddy compared with the outer area of the eddy (the reference site). We speculate that the peculiar feature of excess 234Th in the surface layer was caused by horizontal transport of POC into the eddy and consequent POC degradation and release of particulate 234Th to a dissolved form. However, in 2020, lower POC concentrations with 234Th deficiency were observed in both cyclonic and anticyclonic eddies relative to the reference site. In both years, POC export was lower in the cores of the anticyclonic and cyclonic eddies relative to the reference site. We propose that severe nutrient depletion in the upper 150 m layer hindered nutrient supply by vertical water movement in the eddies. Despite the low POC export at 100 m depth, POC export at 500 m depth was comparable to values observed at 500 m depth at Station Papa in the more productive northeastern Pacific region. Our results imply that POC export into the deep ocean interior in this region may not be as low as expected from the low primary productivity in the euphotic zone.